Observational Study of Recurrent Jets: Evolution of Magnetic Flux, Current, and Helicity - Chang Zhou; Yang Guo; Guoyin Chen; Ye Qiu; M.D. Ding (The Astrophysical Journal)
We observed three recurrent blowout jets in an active region with the Atmospheric Imaging Assembly (AIA) aboard the Solar Dynamics Observatory. Using Helioseismic Magnetic Imager data we found that the magnetic flux of an emerging negative pole increases steadily before declining just as the jets erupt. Certain physical quantities, such as the total unsigned vertical current, align with the periodicity of the jets. The differential affine velocity of vector magnetograms reveals strong shear around the negative pole. The Doppler velocity map, calculated from the H α spectra observed by the Chinese H α Solar Explorer, shows upflows with large initial velocity before they can be observed by AIA. The magnetic field derived from the nonlinear force-free field (NLFFF) model suggests a topology akin to a fan–spine structure, consistent with AIA images. We calculated the evolution of the volumetric helicity ratio using the NLFFF model and found its phase aligns with the jet flux in AIA 171 Å. These results suggest that recurrent jets may be triggered by the accumulation and release of energy and helicity, driven by emergence, shearing, and cancellation of photospheric magnetic field.